Hydrogen production using advanced reactors by steam methane reforming: A review - Ganguli, Arijit; Bhatt, Viraj (Frontiers in Thermal Engineering, 2023)
The present review focuses on the current progress on Methane Steam Reforming (MSR) using methane and methanol with an emphasis on MSR carried out in four novel reactors namely membrane reactors, sorption-enhanced steam methane reactors and micro-reactors. Some emphasis has also been provided on modeling and catalyst development advances have also been in this review. Important parameters like residence time, surface area, scale-up, coke formation, conversion, space velocity, and cost for each of these reactors have been evaluated. Micro-reactors have shown considerable promise in most of the parameters. This review promises to be a precursor for a more comprehensive review on the selection of reactors stages for newer process plants for steam methane reforming.